L1 Legacy SBAS 대비 DFMC SBAS 메시지 구조 차이에 대한 기술적 고찰 - 이진아; 조용래; 김동욱; 박병운; Jina Lee; Yongrae Jo; Donguk Kim; Byungwoon Park (Journal of Positioning, Navigation, and Timing, 2025)
The Dual-Frequency Multi-Constellation (DFMC) Satellite-Based Augmentation System (SBAS) is a next-generation augmentation system that supports L1/L5 dual-frequency signals and multiple constellations, including GPS, GLONASS, Galileo, and BeiDou, whereas the legacy L1 SBAS operates on the L1 C/A single frequency and supports only GPS. DFMC SBAS employs ionosphere-free linear combination (IFLC) to eliminate first-order ionospheric delay errors and does not require an ionospheric correction message. Furthermore, Fast Correction (FC) messages have been removed from DFMC SBAS due to improved satellite clock stability and the discontinuation of Selective Availability (SA), which allows for more efficient use of bandwidth. With these structural improvements DFMC SBAS can support up to 92 satellites across multiple constellations, whereas the L1 legacy SBAS supported only up to 51 satellites. In this study, we provide a detailed comparison between L1 SBAS and DFMC SBAS, focusing on the differences in correction parameters and message structure. Key enhancements of DFMC SBAS include the integration of correction and integrity data into a single message (MT 32) and a flexible integrity broadcasting structure (MT 34-36). These refinements simplify the message structure, expand service coverage, and significantly improve integrity and positioning performance, particularly in regions with high ionospheric variability.